An evaluation of the use of alcohol fuels in SI engines in terms of performance, emission and combustion characteristics: A review - SAYIN, CENK (ELSEVIER SCI LTD, 2021)
Vehicles powered by fossil-fuels cause to increase harmful gases in the environment and decrease petroleum reserves. To minimize these damages, many researchers submitted that one of the alternative fuels which could obtain desired performance and release minimum rates of exhaust emissions in spark-ignition (SI) engines is alcohol fuel, and they carried out many experimental studies. In this review study, experimental studies which indicate the changes in performance parameters, emissions such as hydrocarbon (HC), carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxide (NOx), and combustion characteristics by using alcohol fuel in SI engines were investigated in detail and the increments and decrements in related parameters were indicated in separated tables. In addition, the graphs which indicate how much alteration obtained by using what kind of alcohol and what amount of alcohol in comparison with using gasoline were created.
Keywords: Methanol; Ethanol; Iso-Propanol; Iso-Butanol; Gasoline; SI Engine; SPARK-IGNITION ENGINE; ETHANOL-METHANOL-GASOLINE; ISO-BUTANOL ADDITIVES; N-BUTANOL; EXHAUST EMISSIONS; OPERATING PARAMETERS; POLLUTANT EMISSIONS; COMPRESSION RATIO; PURE GASOLINE; BLENDS